Abnormal MRI signal in the rigid form of Huntington's disease. Issue 10 (October 1991) - Savoiardo, M; Strada, L; Oliva, D; Girotti, F; D'Incerti, L
Abstract : Eighteen patients with Huntington's disease (HD) were examined with MRI. Eleven had the common hyperkinetic form, seven had the rigid variant. All seven patients with rigid HD had increased signal intensity in the neostriatum in intermediate and T2-weighted images. Only one hyperkinetic HD had similar findings. In all the other cases, signal abnormalities were questionable or absent. Histological differences that account for differences in signal intensity may therefore lie in the caudate nucleus and putamen. Age of onset may be important, since the rigid patients were younger. Follow up studies may help in understanding these signal differences.